Generalized approach to assess and characterise the impact of solar PV on LV networks - Almeida D.; Abeysinghe S.; Ekanayake M.P.; Godaliyadda R.I.; Ekanayake J.; Pasupuleti J. (Elsevier Ltd, 2023)
Intelligent systems; Solar power generation; Stochastic models; Stochastic systems; Voltage distribution measurement; Low voltage distribution network; Mean absolute deviations; Monte Carlo techniques; Solar photovoltaics; Stochastic evaluations; Synthetic networks; Voltage unbalance factors; Voltage unbalances; Monte Carlo methods